PENGEMBANGAN KURIKULUM PAI BERBASIS MULTIKULTURAL - Ahmad Faruq; Ahmad Taufiq Hidayatullah; Nanang Budianto (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
Indonesia is a country with diverse religions, cultures, ethnicities, and traditions. This condition makes Indonesian society live in a pluralistic and multicultural environment. In reality, social conflicts in the name of religion still frequently occur, including violence, destruction of places of worship, and mutual suspicion among community groups. This indicates that religious education has not fully succeeded in instilling the values of tolerance, mutual respect, and peaceful coexistence amidst differences. This study aims to explain the importance of developing a multicultural-based Islamic Religious Education curriculum in fostering tolerance and harmonious social life. The method used in this research is a literature study by examining various theories, concepts, and perspectives regarding multicultural education. The results of the study show that multicultural education can serve as a solution in reducing social conflicts and instilling the values of justice, democracy, and respect for cultural and religious diversity. Through an inclusive curriculum and humanistic learning approaches, students are expected to understand the importance of living peacefully within a diverse society. In addition, teachers play an important role in instilling attitudes of tolerance, empathy, and respect for differences. Therefore, the development of a multicultural-based Islamic Religious Education curriculum becomes one of the strategic steps in building a moderate, open-minded generation capable of maintaining national unity.